Modified Ride-On Cars and Young Children with Disabilities: Effects of Combining Mobility and Social Training - Huang, Hsiang-Han; Chen, Yi-Mei; Huang, Hsuan-Wen; Shih, Ming-Ke; Hsieh, Yu-Hsin; Chen, Chia-Ling (Frontiers in Pediatrics, 2018)
Background: Research has shown that the use of power mobility devices (PMDs) is safe and beneficial for motor and cognitive development in children with motor disabilities; nevertheless, strong evidence of the benefits for social skill development is limited. This study aimed to examine the effects of combining ride-on car training with an adult-directed, social interaction program in a hospital-based environment on mobility and social functions in young children with motor disabilities. Methods: This study used a prospective, nonequivalent pretest–posttest control group design. Twenty-nine young children with motor disabilities, aged between 1 and 3 years, were recruited from local hospitals in Taiwan. The treatment group (n=15) underwent 2-hour ride-on car training sessions twice per week for a total of 9 weeks in the hospital environment. The control group (n=14) underwent a 9-week home education program (mean: 200 minutes/week) focusing on mobility and social skills training. The Chinese version of the Pediatric Evaluation of Disability Inventory, Parenting Stress Index, and Goal Achievement Scale were administered to all participants before and after the intervention, and at the end of the 9-week follow-up phase. Results: Mobility and social functions significantly improved in both groups after the 9-week intervention, but this improvement was not maintained at the follow-up phase. The treatment group showed significantly better improvement in social function, parenting stress levels, and goal achievement than the control group at posttest. Conclusions: This two-group design study showed the benefits of combining a ride-on car use with a family-centered, structured, social interaction program for positive impacts on mobility, social function, and parenting stress levels. The combination of a modified ride-on car and a social training program has the potential to enhance socialization in young children with motor disabilities. This trial was registered in the ClinicalTrials.gov: NCT02527499.